The mediating role of corporate image relationship between SERVQUAL and auditee satisfaction: The study of smalls and medium enterprise in Malaysia - Ismail, Ashari; Bakri, Mohammed Hariri; Nordin, Mohd Norazmi; Othman, Habibullah; Abdul Adis, Azaze-Azizi (Science Research Society, 2021)
This research aims to analyze the possible effects of audit firms' service quality on auditee satisfaction and the mediating role of SMP firms' corporate image in receiving audit services in Malaysia. Raw data were collected used structured questionnaires through email communication. The collected data were analyzed first using descriptive statistics, followed by correlation analysis to establish the mediating effects of the corporate image between the dependent and independent variables. The study found that only empathy of service quality has a significant relationship with corporate image and corporate image also a significant relationship toward auditee satisfaction.In another finding, the researchers found an entire mediating effect relationship of the corporate image between assurance and auditee satisfaction.Research such as this is deemed essential to manage SME firms and audit firms alongside academics who may want to pursue the subject matter further. From the recent finding, an audit firm should be given the attention of Assurance and empathy of SERVQUAL and corporate image variable if they need to survive in the competitive environment of the economy facing the world of the pandemic of Covid-19. The research findings are also imperative to scholars by adding current knowledge on service quality,internal audit and risk management. Nonetheless, its sample size limits the study. Therefore, the results do not represent the whole business organization because it only limited to smalls and medium enterprise firms.